HUKUM MENYEMBELIH HEWAN UNGGAS ORANG LAIN KARENA MENGGANGGU DAN MERUSAK PERSAWAHAN - Fazri Rahmadani (INTELIGENSIA MEDIA, 2023)
This study discusses the law of slaughtering poultry belonging to people because it damages or disturbs rice fields. The research is interesting because events occur in the community and the community does not know the law regarding it, so research is needed. The study used library research methods based on references, literature and books on Islamic fiqh law. Based on the results of the study it was found that the legal origin of slaughtering poultry belonging to other people is unlawful or prohibited. But the law may change according to the circumstances in the field. The similarities with other laws can be related to the law of ownership.